LARRI: A Language-Based Maintenance and Repair Assistant - Bohus, Dan; Rudnicky, Alexander I. (IDS-2002, Kloster Irsee, Germany, 2002)
LARRI (Language-based Agent for Retrieval of Repair Information) is a dialog-based system for support of maintenance and repair domains, characterized by large amounts of documentation and by procedural information. LARRI is based on an architecture developed by Carnegie Mellon University for the DARPA Communicator program and is integrated with a wearable computer system developed by the Wearable Computing group at Carnegie Mellon University. LARRI adapts a dialog-management architecture developed and optimized for a telephone-based problem solving task (travel planning), and applies it to a very different domain – aircraft maintenance. The system was taken on a field trial on two occasions where it was used by professional aircraft mechanics. We found that our architecture, AGENDA, extended readily to a multi-modal and multi-media framework. At the same time we found that assumptions that were reasonable in a services domain turn out to be inappropriate for a maintenance domain. Apart from the need to manage integration between input modes and output modalities, we found that the system needed to support multiple categories of tasks and that a different balance between user and system goals was required. A significant problem in the maintenance domain is the need to assimilate and make available for language processing appropriate domain information.